VISUALISASI INFORMASI GEOSPASIAL TEMATIK TUMBUH-TUMBUHAN BERNILAI ILMIAH KEBUN RAYA BOGOR - Sri Handoyo; Fiska Sari Dewi (Universitas Sebelas Maret, 2011)
ABSTRACT Bogor Botanical Garden (BBG) is one of many important assets of Indonesia. It has very wide range of botanical collection that have high scientific values. Up to present there are only line maps available to visualize the BBG, and none of them available in the form of image maps yet. To completely and clearly present the information of the BBG, a satellite remote sensing IKONOS imagery is required to visualize the thematic geospatial information on a map at the scale of 1:5.000. The aim of the research project is to visualize the thematic geospatial information of the scientific botanical garden on a 1:5.000 scale image map.Data of thematic geospatial information of the scientific botanical garden were collected from the old maps of the BBG and the catalogues of the Indonesian Institution of Sciences. Other data of line maps and IKONOS imageries were processed in a series of phases i.e. geometric correction, determination of the 321 band, data editing and updating, and cartographic designs in one and two levels, including the distribution of questionnaires to test the design out and get the feed back from the respondents.Result of the visualization is considered substantially sufficient, cartographically correct and complete at scale of 1:5.000, and aesthetically interesting in terms of tourism due to the acceptance of the entire 30 designed image symbols. Key words : bambu visualization, image map, bogor botanical garden, cartography, ikonos imagery.